Correction: Evaluating the sustainability, scalability, and replicability of an STH transmission interruption intervention: The DeWorm3 implementation science protocol. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2018)
[This corrects the article DOI: 10.1371/journal.pntd.0005988.].